Therapeutic experience with elderly people caregivers of a chronic sick relative - Bail Pupko, Vera (2007)
This article presents a therapeutic experience illustrating a wide range of aspects of an intervention carried out in some public hospitals of Buenos Aires city, Argentina. The experience was directed to susceptible groups with the aim to improve the effectiveness of the tackling mechanisms and the social support networks, as well as to reduce the uncertainty. The studied group was formed by seven chronic sick elderly people who take cure of a relative. The sessions were recorded and emergent categories of the narrative presented were constructed. The conclusion is that the elderly people are usually the people receiving care, but when they are caregivers, they need additional support that health institution cannot always give them.